Pengaruh Fungi Mikoriza Arbuskula Indigenus Terhadap Pertumbuhan dan Produksi Jarak Pagar (Jatropha Curcas L.) di Lahan Kritis - Muzakkir Muzakkir (Fakultas Pertanian Universitas Tamansiswa Padang, 2012)
The extent of critical land in Indonesia has continues to grow and reached 30 million hectares. In West Sumatra it has reached 1.275.190, 90 hectares. This is a warm to both the environment and sustainable agricultural development. To overcome this problem, it is possible to use the indigenous arbuscula mycorrhizal fungi (AMF) to cultivate plants to economic value such as caster bean (Jatropha curcas L.) that can adapt to such critical land. The study aims to determine the effect of different AMF isolates on the growth and production of caster bean on critical lands. The experimental results show, a mixture of three isolates (Glomus sp2+ Acaulospora sp1 + Gigaspora sp1) is better than a mixture of two isolates of AMF in improving P uptake and growth (plant height) of caster bean. Isolates the effect of single Glomus sp2 higher than Gigaspora sp1, and Acaulospora sp1. AMF inoculation indigenus isolates, the effect is better than without AMF inoculation in increasing the uptake of P, and the growth of jcaster bean on degraded land. During the first year of growth on critical land at Tanjung Alai Solok, West Sumatera caster beans inoculated with a mixture of the of three isolates (Glomus. sp2, Acaulospora sp1, Gigaspora sp1) produced 170,47 grams of dry seeds per tree, equivalent to 426,17 kg ha-1 or 0,43 tons ha-1